Adrenal Schwannomas: Rare Tumor of the Retroperitoneum. (26th May 2015) - Grasso, Emanuele; Simone, Michele
Abstract : Schwannoma is a benign neurogenic tumor originating from Schwann cells. These produce the myelin sheath that covers peripheral nerves that are often affected. This latter localization is extremely rare, and only a few case reports can be found in the medical literature. Studies have shown that approximately 0.5% to 5% of schwannomas are retroperitoneal, constituting 0.2% of adrenal incidental tumors. These usually present as incidental findings, nonsecreting adrenal masses in asymptomatic patients. Diagnosis of a schwannoma is based on detection of spindle cells with Antoni A and Antoni B regions in histological sections and positive staining for S-100 protein by immunohistochemical analysis. We report a case of an incidentally identified during an abdominal ultrasound examination with schwannoma localized in the left adrenal gland.